The Optimal Bonus-Malus System: Case of The Democratic Republic of Congo - Bukanga Maheshe, Crispin; Rostin, Mabela Makengo Matendo (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2024)
AbstractAutomobile insurance is required in most African nations, and it is the most significant branch in the Democratic Republic of the Congo (DRC); if the automobile branches are poorly managed, this could even result in the insurance company's insolvency. A priori pricing does not improve the danger parameter (the variance), which measures the difference between the estimated model and the observed reality; since the pricing characteristics do not take into account the driver's experience, the portfolio remains heterogeneous. To ensure the insurer's solvency, a more refined post-season pricing model is necessary, one that accounts for driver behavior. Our research introduces an innovative approach to a posteriori pricing in the DRC, using the Bonus-Malus System. In this model, policyholders are divided into classes based on the frequency of claims to preserve the insurer's solvency. The Bonus-Malus System will serve as the basis for the automobile portfolio's a posteriori pricing: the driver who has not declared a claim receives a reduction in his premium in the year tn+1 (Bonus), and the wrong driver who has declared more than one claim will see his premium increased to the year tn+1 (Malus). Inspired by models from Belgium (the class model) and France (the multiplicative model), we develop a Bonus-Malus model applicable to the DRC. The results found that the class system outperforms the other model for the DRC due to its clarity and fairness. We also emphasize the need for SONAS to centralize data to effectively implement this system and optimize motor vehicle claim management.Keywords: bonus-malus; insurance policy; risk; frequency of claims; prior pricing; ex post facto pricing. AbstrakAsuransi mobil diwajibkan di sebagian besar negara Afrika, dan merupakan cabang yang paling signifikan; di Republik Demokratik Kongo (DRC),. Jika cabang mobil dikelola dengan buruk, hal ini bahkan dapat mengakibatkan kebangkrutan perusahaan asuransi. Penetapan harga secara apriori tidak memperbaiki parameter bahaya (varians) yang mengukur perbedaan antara model yang diestimasi dengan kenyataan yang diamati, karena karakteristik penetapan harga tidak memperhitungkan pengalaman pengemudi, maka portofolio tetap heterogen. Untuk memastikan solvabilitas perusahaan asuransi, diperlukan model penetapan harga pasca musim yang lebih terperinci, yang memperhitungkan perilaku pengemudi. Penelitian kami memperkenalkan pendekatan inovatif untuk penetapan harga a posteriori di DRC, menggunakan Sistem Bonus-Malus. Dalam model ini, pemegang polis dibagi menjadi beberapa kelas berdasarkan frekuensi klaim, untuk menjaga solvabilitas perusahaan asuransi. Sistem Bonus-Malus akan menjadi dasar penetapan harga a posteriori portofolio kendaraan bermotor: pengemudi yang belum pernah mengajukan klaim akan menerima pengurangan premi pada tahun tn+1 (Bonus) dan pengemudi nakal yang mengajukan lebih dari satu klaim akan mengalami kenaikan premi pada tahun tn+1 (Malus). Terinspirasi oleh model dari Belgia (model kelas) dan Prancis (model multiplikatif), kami mengembangkan model Bonus-Malus yang dapat diterapkan di DRC. Hasil penelitian menemukan bahwa sistem kelas lebih unggul dibandingkan model lain untuk DRC karena kejelasan dan keadilan. Kami juga menekankan perlunya SONAS untuk mengkonsolidasi data guna mengimplementasikan sistem ini secara efektif dan mengoptimalkan manajemen klaim kendaraan bermotor.Kata Kunci: bonus-malus; polis asuransi; risiko; frekuensi klaim; penetapan harga sebelumnya; penetapan harga ex post facto.2020MSC: 91G05